2021
DOI: 10.1080/21655979.2021.1999366
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Omarigliptin on promoting osteoblastic differentiation

Abstract: Osteoporosis significantly impacts the normal life of the elderly and is reported to be closely related to dysfunction of osteoblastic differentiation. Runt-related transcription factor-2 (Runx2) is a critical transcriptional factor involved in the regulation of osteoblast differentiation. Omarigliptin is a novel dipeptidyl peptidase-4 (DDP-4) inhibitor and this study proposes to probe into its possible therapeutic function against Osteoporosis by investigating its impacts on osteoblastic differentiation. Oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…ALP activity is associated with osteoblast differentiation and greatly influences the process of cell matrix mineralization in osteoblasts. 18 In the normal medium, we observed the effects of MAO, MAO+PDA, and MAO+PDA+NC coatings on ALP activity during culture, in which ALP activity was significantly increased in the MAO+PDA+NC group ( Figure 7E and F ), which further demonstrated that the MAO+PDA+NC composite coating has better osteoinductive activity.
Figure 7 Osteogenic induction of the different coatings.
…”
Section: Resultsmentioning
confidence: 64%
“…ALP activity is associated with osteoblast differentiation and greatly influences the process of cell matrix mineralization in osteoblasts. 18 In the normal medium, we observed the effects of MAO, MAO+PDA, and MAO+PDA+NC coatings on ALP activity during culture, in which ALP activity was significantly increased in the MAO+PDA+NC group ( Figure 7E and F ), which further demonstrated that the MAO+PDA+NC composite coating has better osteoinductive activity.
Figure 7 Osteogenic induction of the different coatings.
…”
Section: Resultsmentioning
confidence: 64%
“…It has been found that osteoblast differentiation requires the classical Wnt/β-catenin signaling pathway ( 14 ). It has been reported that some osteoblasts contain ALP, which can be used as a biochemical marker to assess bone formation ( 34 ); however, mechanical loading increases ALP activity ( 35 ). Thus, in the present study, it was demonstrated using ALP staining (AZO method) that the number of ALP-positive cells in the subchondral bone specimens, to be increased during the progression of OA from mild to moderate; in addition, in severe OA, there was no significant increase in active osteoblasts compared with that in moderate OA.…”
Section: Discussionmentioning
confidence: 99%
“…All cell cultures were maintained in humidified 5% CO 2 incubators at 37°C. The growth of osteoblasts was observed under an inverted-phase contrast microscope [ 21 ].…”
Section: Methodsmentioning
confidence: 99%